2013 IEEE Energy Conversion Congress and Exposition 2013
DOI: 10.1109/ecce.2013.6646891
|View full text |Cite
|
Sign up to set email alerts
|

Active current balancing for parallel-connected silicon carbide MOSFETs

Abstract: In high power applications of silicon carbide (SiC) MOSFETs where parallelism is employed, current unbalance can occur and affect the performance and reliability of the power devices. In this paper, factors which cause current unbalance in these devices are analyzed. Among them, the threshold voltage mismatch is identified as a major factor for dynamic current unbalance. The threshold distribution of SiC MOSFETs is investigated, and its effect on current balance is studied in experiments. Based on these analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 10 publications
(10 reference statements)
0
48
0
Order By: Relevance
“…Some other active control strategies have been published in [7], [10], and [11]. An active voltage control technique using dV ce /dt in series-connected IGBTs is proposed in [7].…”
Section: Introductionmentioning
confidence: 99%
“…Some other active control strategies have been published in [7], [10], and [11]. An active voltage control technique using dV ce /dt in series-connected IGBTs is proposed in [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the asymmetric distribution of parasitic inductances in the paralleled devices can cause uneven current sharing during turn-on and turnoff processes, which, in turn, causes uneven switchingloss distribution. In order to balance the current among the paralleled devices, special efforts have to be put on either the layout of circuit or the driver designs (both hardware and software) [3] [4]. This could increase the complexity and cost of the system.…”
Section: Instructionmentioning
confidence: 99%
“…6 shows the control scheme for the multiphase drive. Basically vector control is implemented according to (4) and (5). In addition, one phase open circuit fault is considered in the simulation.…”
Section: System Modelingmentioning
confidence: 99%
“…The study of device and circuit mismatch of paralleled SiC MOSFETs has been reported as well [8]- [9]. However, these studies on the device parallel operation do not apply directly to the cascode GaN HEMT.…”
Section: Introductionmentioning
confidence: 99%